2007
DOI: 10.1063/1.2773755
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling in Ge nanoparticles

Abstract: Ferromagnetism in Ge nanoparticles fabricated by inert gas condensation was investigated. The magnetization was influenced by both the size and the density of Ge nanoparticles. The size was determined by the helium pressure and the density was controlled by depositing Ge nanoparticles on Si substrates at different locations. As the density was increased, the interparticle distance was reduced, which enhanced the magnetic coupling among Ge nanoparticles. The magnetism in Ge nanoparticles was attributed to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The ferromagnetic behaviors of the undoped GaAs NWs are quite surprising. Recently, the size-dependent ferromagnetism of Ge nanoparticles (deposited on polystyrene or Si substrates) has been reported . Our research group also observed room-temperature ferromagnetic properties for Ge NWs, and suggested that this originated from the existence of uncompensated spins and surface anisotropy, because of the high surface/volume ratio .…”
Section: Resultsmentioning
confidence: 53%
“…The ferromagnetic behaviors of the undoped GaAs NWs are quite surprising. Recently, the size-dependent ferromagnetism of Ge nanoparticles (deposited on polystyrene or Si substrates) has been reported . Our research group also observed room-temperature ferromagnetic properties for Ge NWs, and suggested that this originated from the existence of uncompensated spins and surface anisotropy, because of the high surface/volume ratio .…”
Section: Resultsmentioning
confidence: 53%
“…The ferromagnetic behaviors of undoped Ge NWs are quite surprising. Recently, however, the size-dependent ferromagnetism of Ge nanoparticles (deposited on polystyrene or Si substrates) has been reported . The authors suggested that this was due to the occurrence of the quantum confinement effect owing to their large Bohr radius (∼17 nm).…”
Section: Resultsmentioning
confidence: 99%
“…While high-temperature ferromagnetism has never been confirmed in GeMn films with properly diluted magnetic defects, unusual magnetic properties of Ge 1−x Mn x quasi-onedimensional ͑1D͒ nanostructures [11][12][13][14][15][16] and even intrinsic ferromagnetism in magnetically undoped Ge quantum dots 17,18 have been demonstrated recently. Perfect dilution of Mn ions in the host accompanied by a high Curie temperature, correlation between electrical and magnetic properties, existence of charge and spin carriers in a magnetically ordered lattice, [19][20][21] and other remarkable features of these systems make them attractive for spintronic applications.…”
Section: Introductionmentioning
confidence: 98%